2018
DOI: 10.1111/psyg.12375
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and loneliness. Findings from a longitudinal population‐based study in the second half of life in Germany

Abstract: Aim:Little is known about whether changes to obesity are associated with changes in loneliness scores. Therefore, using a longitudinal approach, we aimed to determine whether the onset of obesity (explanatory variable) is associated with changes in loneliness (outcome measure) among older adults.Methods: For the present study, data from wave 2 (2002) to wave 5 (2014) of the German Ageing Survey were analyzed. This is a representative sample of community-dwelling individuals in Germany (≥40 years). A validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
0
25
2
Order By: Relevance
“… 25 In total, n=6 studies were included in the final synthesis of our current systematic review. 8 , 16–19 , 21 Key characteristics and main findings are displayed in Table 2 . Adjusted results (if reported) are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 In total, n=6 studies were included in the final synthesis of our current systematic review. 8 , 16–19 , 21 Key characteristics and main findings are displayed in Table 2 . Adjusted results (if reported) are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“… Hajek (2018) 21 Germany BMI > 30 kg/m 2 scale generated by Bude and Lantermann (four items) cross-sectional German Ageing Survey n=7838 M=64.4 SD=11.2 range not specified 51.0% As linear regression revealed, obesity was related to social exclusion only among women (ß=−0.1, p<0.05). Hajek (2019) 8 Germany BMI > 30 kg/m 2 Loneliness scale developed by Gierveld and van Tilburg (six items) Longitudinal (four waves, 2002–2014) German Ageing Survey n=21,099 M=63.4 SD=11.5 range not specified 49.2% Regarding fixed-effects regression, obesity was positively associated with loneliness among men (ß=0.1, p<0.05), but not among women. Rotenberg (2017) 18 United Kingdom BMI > 30 kg/m 2 UCLA-R Loneliness Scale (20 items) Cross-sectional Undergraduates from a mid-size university n=137 M=21.8 SD=4.7 18–57 58.4% An ANOVA revealed that obesity was associated with increased levels of loneliness (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cultural measures, the individual's past experiences and even that from previous generations may generate complex interaction and synergies with the biological ageing process and social life (Ambeskovic et al, 2020;Brown et al, 2017;Faraji et al, 2017a). Also, this relationship is strongly influenced by pre-existing health conditions, gender, personality and culture (Hajek and König, 2019;Ormstad et al, 2020;Ward et al, 2018).…”
Section: Ageing Social Distancing and Covid-19: The Two-hit Model Of Stressmentioning
confidence: 99%
“…Excess weight (overweight and obesity) is an important risk factor for various chronic conditions [1]. Moreover, it is, among other things, associated with loneliness [2], poorer mental health [3], sickness absence (sick leave days and long-term absenteeism) [4], and increased health care use or costs [5]. In many countries prevalence rates of obesity are quite high [6].…”
Section: Introductionmentioning
confidence: 99%